Risk Management in Islamic Education Transformation: RAMESPA Pagambiran's Strategy for Building Innovation and Sustainable Collaboration - Aldi, Muhammad; Khairanis, Retisfa; Kawakip, Akhmad Nurul; Mustikawan, Alfin; Al Aziz, Sulthan (Proceeding of International Conference on Islamic Education (ICIED); Vol 10 No 1 (2025): Proceeding of International Conference on Islamic Education (ICIED)DO - 10.18860/icied.v10i1.3606, 2025)
The transformation of Islamic education management in mosque youth communities requires strategies that encourage innovation, collaboration, and sustainability. This study aims to analyze RAMESPA Pagambiran's risk management to improve the effectiveness of Islamic education programs. The research method used a quantitative approach with a risk map scale-based survey of RAMESPA members. Four risk dimensions were analyzed: operational, financial, human resources (HR), and collaboration/partnership, with an average score of 1–5 for each indicator, then calculated into a total score. The results show operational risk of 12 (high), HR of 9–12 (high), financial of 16–20 (critical), and collaboration of 9 (moderate). Financial risk, particularly financial management with a score of 20, is a critical factor. HR risk emphasizes the importance of improving the competence and motivation of members, while collaboration risk indicates the need for strategic networks to support innovation and sustainability. In conclusion, systematic and sustainable risk management enables RAMESPA Pagambiran to run Islamic education programs effectively, innovatively, and with a social impact. Mitigation strategies include strengthening member capacity, diversifying funding sources, and developing strategic partnerships to expand the contribution of Islamic preaching and education in the community.